A new species of hastospiculum skrjabin (spirurida: Diplotriaenidae) parasite of xenodon merremii (walger in spix) (serpentes: Dipsadidae) from northeastern brazil - Ferreira-Silva, Cristiana [UNESP]; Alcantara, Edna P.; Ávila, Robson W. [UNESP]; Silva, Reinaldo J. [UNESP] (Magnolia Press, 2020)
A new nematode species of the Diplotriaenidae is described from the Neotropical region. The species was found infecting the body cavity of the snake Xenodon merremii (Wagler in Spix) collected in the municipality of Barbalha, Ceará State, Northeastern Brazil. Hastospiculum nordestinum n. sp. differs from the congeners by combining the following characters: caudal end ornamented with lateral alae not surrounding the tail end and not connected, supported by eight pairs of pedunculated papillae (three precloacal, one paracloacal, and four postcloacal pairs) and three adcloacal sessile papillae, and left spicule length 719.6 902.4 ?m. Besides the description of Hastospiculum nordestinum n. sp., a species list and a dichotomous key to Hastospiculum are provided.
Keywords: Hastospiculum nordestinum n. sp.; Nematoda; Neotropical region; parasite; snake; taxonomy